A Fatigue Cohesive Law‐Embedded Finite‐Discrete Element Method for Pulsed Hydraulic Fracture Simulation - Wei, Xuanchun; Wang, Lei; Li, Yancao; Ding, Jingtao; Zhang, Zhennan (International journal for numerical and analytical methods in geomechanics, 2025)
ABSTRACT The pulsed hydraulic fracture (PHF) is a stimulation technique of reservoir, which can lower breakdown pressure by generating fatigue fracture. In this study, a fatigue cohesive law is proposed and embedded into the finite‐discrete element method (FDEM) to describe the fatigue failure of the interface under cyclic loading. The fatigue is assumed to result from the accumulation of plastic deformation, whose increment is related to the traction variation range of each cycle and the total plastic deformation. The proposed fatigue cohesive law is validated by the uniaxial compression and mixed‐mode three‐point bending test simulation. Then this fatigue cohesive law is embedded into a fully hydraulic–mechanical coupled FDEM to simulate the PHF. The influence of loading scheme, flow rate, frequency, viscosity and natural fracture density on PHF behaviors is discussed. The results suggest that both the pressure‐ and injection rate–controlled PHF can reduce the breakdown pressure. The flow rate, frequency, and viscosity have a great impact on the performance of PHF. The natural fractures surrounding a hydraulic fracture (HF) can be gradually activated under cyclic injection. The activated natural fractures contribute to the complicated HF network. These results indicate that the proposed fatigue cohesive model can effectively simulate the fatigue fracture of rock and HF propagation under cyclic injection.